2018
DOI: 10.1186/s13756-018-0341-1
|View full text |Cite
|
Sign up to set email alerts
|

Pet owner and vet interactions: exploring the drivers of AMR

Abstract: BackgroundAntimicrobial resistance (AMR) is a growing public health problem across the world. As the negative consequences of AMR become apparent at local, national and international levels, more attention is being focussed on the variety of mechanisms by which AMR is potentiated. We explore how interactions between pet owners and veterinarians represent a key arena in which AMR-related behaviours can be shaped.MethodsIn depth semi-structured interviews were carried out with pet owners (n = 23) and vets (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(135 citation statements)
references
References 20 publications
7
123
2
3
Order By: Relevance
“…Barriers to appropriate antibiotic use and drivers of AMR in companion animals have been explored in many recent studies ( 20 23 ), with this area of veterinary medicine of increasing interest in relation to AMR and antibiotic use. Results in this study support many findings from previous studies, in particular the point that open, adequate communication between vets and pet owners needs support to ensure appropriate antibiotic and antimicrobial use ( 21 ), and to avoid misinterpretation of intentions or motivations. Communication between vets and owners was evidently inadequate in many of the examples given both by vets and pet owners in this study and showed conflicting perceptions of responsibility regarding antibiotic prescription and use.…”
Section: Discussionsupporting
confidence: 87%
“…Barriers to appropriate antibiotic use and drivers of AMR in companion animals have been explored in many recent studies ( 20 23 ), with this area of veterinary medicine of increasing interest in relation to AMR and antibiotic use. Results in this study support many findings from previous studies, in particular the point that open, adequate communication between vets and pet owners needs support to ensure appropriate antibiotic and antimicrobial use ( 21 ), and to avoid misinterpretation of intentions or motivations. Communication between vets and owners was evidently inadequate in many of the examples given both by vets and pet owners in this study and showed conflicting perceptions of responsibility regarding antibiotic prescription and use.…”
Section: Discussionsupporting
confidence: 87%
“…The importance of an animal owner or caretaker regarding AMU is confirmed by other studies on companion animals as well as on farm animals (Mateus et al, 2014;Speksnijder et al, 2015a;Coyne et al, 2016;Chipangura et al, 2017;Hardefeldt et al, 2017;Smith et al, 2018). A recent study on AM prescribing in companion animals states that veterinarian's perceptions of client expectations might drive inappropriate AM prescribing (Currie et al, 2018).…”
Section: Discussionmentioning
confidence: 81%
“…Previous research has highlighted the importance of social and cultural context alongside personal experience for understanding specific attitudes towards vaccination, 25,32 and similar contextual influences have been discussed in the context of antibiotic use. [35][36][37] The future research indicated here should be cognisant of these influences, and consider medical and veterinary care contexts such as parental decision-making and veterinarian-client communication as well as broader dynamics within the general population regarding antibiotic use as well as vaccine decisions.…”
Section: Higher Vaccine Risk Perceptions Are Associated With Antibiotmentioning
confidence: 99%